2021
DOI: 10.1542/peds.2020-044735
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Use and Outcomes at Children’s Hospitals During the Early COVID-19 Pandemic

Abstract: This is a prepublication version of an article that has undergone peer review and been accepted for publication but is not the final version of record. This paper may be cited using the DOI and date of access. This paper may contain information that has errors in facts, figures, and statements, and will be corrected in the final published version. The journal is providing an early version of this article to expedite access to this information. The American Academy of Pediatrics, the editors, and authors are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 24 publications
5
27
1
Order By: Relevance
“…To our knowledge, this is the first study to examine the long-term (one year since the lockdown started) impact of the COVID-19 pandemic on paediatric health service use for a wide range of health conditions at a large state-wide paediatric healthcare provider. Our findings converge with previous research showing rapidly reduced paediatric health service use following the implementation of the lockdown 1 , 3 , 29 and that the decline for most chronic conditions was only evident during the lockdown. After the lockdown, the service use generally returned to the pre-COVID predicted levels.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…To our knowledge, this is the first study to examine the long-term (one year since the lockdown started) impact of the COVID-19 pandemic on paediatric health service use for a wide range of health conditions at a large state-wide paediatric healthcare provider. Our findings converge with previous research showing rapidly reduced paediatric health service use following the implementation of the lockdown 1 , 3 , 29 and that the decline for most chronic conditions was only evident during the lockdown. After the lockdown, the service use generally returned to the pre-COVID predicted levels.…”
Section: Discussionsupporting
confidence: 91%
“…The immediate return to pre-COVID predicted levels for most chronic health conditions post-lockdown has highlighted the healthcare needs for children affected by chronic conditions. Similar to previous studies, the reduction in health service use was largely related to chronic respiratory conditions such as asthma 6 , 12 , 29 ; while, smaller reductions occurred in cancer and metabolic conditions 3 , . 6 , 29 The duration of decline in health service use related to chronic conditions was shorter in this study than that reported in the US where the reduction in health service use lingered for at least three months with extended pandemic 12 , .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations